Loneliness in middle age and biomarkers of systemic inflammation: Findings from Midlife in the United States. (July 2018) - Nersesian, Paula V.; Han, Hae-Ra; Yenokyan, Gayane; Blumenthal, Roger S.; Nolan, Marie T.; Hladek, Melissa D.; Szanton, Sarah L.
Abstract: Objective: Middle-aged adults who are lonely have an elevated likelihood of death. Systemic inflammation may contribute to these increased odds. Using population-level data, this study tested if systemic inflammation is associated with loneliness in a broad age range of middle-aged adults in the United States. Methods: This study used data from the Midlife in the US (MIDUS) survey Biomarker Project, which collected data on psychological, social, and physiological measures from a sample of middle-aged adults. This sample included the 927 participants who were 35–64 years at Biomarker Project data collection. MIDUS collected baseline data from 1995-1996 and a follow-up survey was conducted from 2004-2006. The baseline Milwaukee sample of African Americans was collected in 2005–2006 and the biomarker database was collected in 2004–2009. Biomarkers were obtained from a fasting blood sample. Self-reported loneliness was categorized as feeling lonely or not feeling lonely. Hierarchical regressions examined the association between biomarkers of systemic inflammation (interleukin-6, fibrinogen, C-reactive protein) and feeling lonely, adjusted for covariates. Results: Twenty-nine percent of the sample reported feeling lonely most or some of the time. There was a positive significant relationship between loneliness and the three systemic inflammation biomarkers after controlling for covariates: interleukin-6 ( n  = 873) ( b [ se ] = 0.07 [0.03], p  = .014); fibrinogen ( n  = 867) ( b [ se ] = 18.24 [7.12], p  = .011); and C-reactive protein ( n  = 867) ( b [ se ] = 0.08 [0.04], p  = .035). Conclusions: Feeling lonely is associated with systemic inflammation in middle-aged community-dwelling US adults. Highlights: Nearly 30% of this US-based sample of middle-aged adults reported feeling lonely. Self-reports of feeling lonely are associated with more inflammation in the body. No difference was found in self-reports of feeling lonely between females and males. Feeling lonely was strongly positively correlated with self-reports of more stress. Positive relationships and social integration correlated negatively with loneliness.